Kepler-410Ab and Transit Timing Variations. Issue Volume 14:Issue S339(2018) (November 2017) - Gajdoš, P.; Parimucha, Š.; Fedurco, M.
Abstract: Our poster presented a new analysis of the transit-time variations displayed by the extrasolar planet Kepler-410Ab. We assumed that the observed changes in the transit times are caused by the gravitational influence of another body in the system. To determine the mass of that perturbing body, we considered the light-time effect and an analytical approximation of the perturbation model. The solutions resulting from both methods gave comparable results, with an orbital period of 970 days and a slightly eccentric orbit for the third body. We proposed two possible models of a perturbing body orbiting a common barycentre with Kepler-410A: a single star with mass of at least 0.906 M⊙, or a binary star with a total component mass of at least 2.15 M⊙ .